FANTASI KELOMPOK PENDUKUNG PRABOWO DI MEDIA SOSIAL PADA DEBAT PEMILIHAN PRESIDEN INDONESIA 2019 - Laskarko Patria (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
This research uses the theory of Symbolic Convergence, with the Subjective-Interpretive paradigm, with the Qualitative approach, and the Fantasy Theme Analysis method. The object of this research is the public audience/netizens who use Youtube-TVONE social media, during the broadcast of the 2019 Presidential Election Debate (Pilpres). Methods of data collection, using Observation and Documentation techniques. Netizens’ comments on Youtube social media at the time of the Debate show, are data that are the object of research. The research data is in the form of comments from netizens who are considered relevant are support presidential candidate Prabowo Subianto. The purpose of this study is to identify and interpret fantasy themes that appear in comments on Youtube. The results showed that fantasy themes that often appear in netizen’s comments are Leadership and Character. The meaning of the imagination of Prabowo’s support group is that the public wants Prabowo to be president, because he has a good character, honest, courageous, assertive, and has a leadership spirit, so he can regulate and discipline state ofcials and realize national economic independence. Prabowo’s support group was convinced that the president had to be replaced, because he did not have a leadership spirit, and the government was now considered less eﬀective, and not pro-people.